Community Empowerment Through Beyond Center And Circle (Bcct) Approach At Sdn Kaplogan 2 - Nur Robithoh; Didik Himmawan (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
The form of community service carried out by students is real work lectures (KKN). In an effort to educate the nation's life, one of the activities that needs to be carried out by KKN students is activities in the field of education. For this reason, teaching activities are carried out with the aim that KKN students are able to compile programs of community service activities in the educational aspect. the role of Real Work College Students in the Field of Education as a Form of Community Service in the Village. This activity can be carried out properly. In education, of course we don't just teach but we also apply the Beyond Center and Circle (BCCT) system in the learning process, because with the BCCT learning process we can develop creative and innovative aspects of child development so that it can be implemented in the learning process. The learning model must be able to stimulate all aspects of the child's intelligence. There are several learning models that can be used in the learning process. One of the learning models proposed here is: The beyond center and circle time (BCCT) learning model. The Beyond Center & Circle times (BCCT) method is a method or approach in providing education that aims to stimulate all aspects of children's intelligence (plural intelligences) through directed play activities.